RESPON HASIL DAN JUMLAH BIJI BUAH SEMANGKA (Citrullus vulgaris) DENGAN APLIKASI HORMON GIBERELIN (GA3) - Wijayanto, Teguh; Yani, Wa Ode Rahzia; Arsana, Made Widana (Jurnal Agroteknos, 2012)
Hormone gibberellin (GA3) is known to be able to increase yield and plays a role in the production of seedless fruits. This research was conducted to determine the effects of GA3 application on yield and quality (seed number) of watermelon. The research was performed at the experimental farm of Agriculture Faculty, University of Halu Oleo. The research was arranged in a Complete Randomized Design (CRD) with a single factor (dose of GA3), consisted of 6 (six) levels, namely: without GA3 application (G0), GA3 100 mg L-1 (G1), GA3 150 mg L-1 (G2), GA3 200 mg L-1 (G3), GA3 250 mg L-1 (G4), and GA3 300 mg L-1 (G5). Each treatment consisted of 4 (four) plants, with 3 replicates, to make an averall 72 experimental units (plants). Research results showed that the application of GA3 significantly influenced the fresh fruit weight, fruit diameter, fuit content diameter, and seed number. Treatment of gibberellin 300 mg L-1 (G5) tended to produce higher yield (fresh fruit weight, fruit diameter, fuit content diameter), while G4 treatment (250 mg L-1) resulted in the lowest number of seeds in the fruit. Despite further research is still needed, this research indicates that the application of gibberellins (GA3) has the potency in increasing the yield of watermelon and improving the quality, in term of the possibility to produce seedless watermelon. Keywords: gibberellins (GA3), fruit yield and quality, seedless fruit, watermelon.